PERSEPSI SERTIFIKASI HALAL DAN MINAT BELI TERHADAP LOYALITAS MEREK: PENDEKATAN MODEL SEM PLS PADA KONSUMEN MILLENIAL INDONESIA - Darmawan, Roy; Ramadhan, Yusuf; Nasihin, A. Khoirun; Sabani, Nurus (JURNAL LENTERA BISNIS, 2026)
Indonesia is the country with the largest Muslim population in the world. The food industry in Indonesia is largely determined by halal certification issued by the Indonesian Ulema Council (MUI). This paper aims to provide information on the influence of halal certification on consumer purchasing interest and loyalty to brands that have halal certification for their food products. The halal industry in Indonesia has grown rapidly in recent years. This has attracted the attention of consumers and industry players who choose halal certification as an indicator of good practices in the Indonesian food industry. In addition to considering halal certification from a religious, safety, and hygiene perspective, it is also important to understand the relationship between these and, of course, its impact on business growth. The method used in this study was Structural Equation Modeling (SEM) with a PLS approach. Millennial respondents consisted of respondents aged 23-41 years. The questionnaire was determined using the Non-Probability Sampling method, and sampling was conducted using Purposive Sampling. Data collection was carried out by distributing questionnaires online using Google Forms and shared via WhatsApp and Instagram. There are various benefits provided by Halal certification. The results of the study show that the halal certification variable has an influence on purchasing interest, and purchasing interest has an influence on brand loyalty.